Long Term Oral Steroid Medication Induce Hip Dislocation in Pediatric : A Case Report (World Journal of Current Medical and Pharmaceutical Research, 2021)
Oral corticosteroids play a major role in the treatment of diseases such as dermatitis. In adults, osteoporosis is a well-known and major complication of oral corticosteroid treatment. A recent study reported that the risk of hip fracture and dislocation was doubled in adults using higher doses of oral corticosteroids. Its findings suggested that the adverse skeletal effects of oral corticosteroids manifest rapidly. Several studies have reported decreased bone density in children taking oral corticosteroids. No studies have evaluated the risk of dislocation in children taking oral corticosteroids.